2006
DOI: 10.1026/0044-3409.214.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Beanspruchungswirkungen von Selbstkontrollanforderungen und Kontrollmöglichkeiten bei der Arbeit

Abstract: Zusammenfassung. An zunehmend mehr Arbeitsplätzen wird heute ein hohes Ausmaß an Selbstkontrolle von den Beschäftigten gefordert. In Anlehnung an das “Demands-Control“-Modell von Karasek (1979) wurde untersucht, ob die beanspruchenden Wirkungen dieser bisher wenig untersuchten Form der Arbeitsbelastung durch situative Spielräume der Kontrolle und Einflussnahme abgeschwächt bzw. moderiert werden. Untersuchungsteilnehmer waren 260 Altenpflegekräfte. Es konnte gezeigt werden, dass zunehmende Selbstkontrollanforde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…In turn, employees who have fewer resources are more likely to bene t from job crafting and experience less ego depletion, leading to lower fatigue and higher vigor at the end of work. Further, our ndings are consistent with previous research results showing that employees who are coping well with self-control demands pro t from high situational control opportunities at work [42].…”
Section: Contributions To the Literaturesupporting
confidence: 92%
“…In turn, employees who have fewer resources are more likely to bene t from job crafting and experience less ego depletion, leading to lower fatigue and higher vigor at the end of work. Further, our ndings are consistent with previous research results showing that employees who are coping well with self-control demands pro t from high situational control opportunities at work [42].…”
Section: Contributions To the Literaturesupporting
confidence: 92%
“…Neubach and Schmidt (2006a) demonstrated that the measured self-control demands correlated positively with health complaints (r ϭ .27), the burnout dimensions of emotional exhaustion (r ϭ .36), and depersonalization (r ϭ .33); and negatively with job satisfaction (r ϭ Ϫ.25). In another study, Neubach and Schmidt (2006b) found further evidence for the assumption that such selfcontrol demands are associated with psychic costs, which did emerge not only in the experience of burnout, but also in a measure of depression (r ϭ .46; see also, Schmidt, Neubach, & Heuer, 2007).…”
Section: Costs Of Self-controlmentioning
confidence: 81%
“…Several studies could demonstrated that for employees who reported low levels of control, self-control demands were positively associated with emotional exhaustion, psychosomatic complaints, and absenteeism as well as negatively related to job satisfaction. By way of contrast, there were less adverse effects of self-control demands on job strain for those who perceived high levels of job control [52,53]. Quite similar buffering effects of control were found in the relationship between emotional dissonance as stressor and burnout [54].…”
Section: Job Controlmentioning
confidence: 74%